2007
DOI: 10.1007/s10126-007-9029-x
|View full text |Cite
|
Sign up to set email alerts
|

Antifouling Activity of Bromotyrosine-Derived Sponge Metabolites and Synthetic Analogues

Abstract: Eighteen brominated sponge-derived metabolites and synthetic analogues were analyzed for antilarval settlement of Balanus improvisus. Only compounds exhibiting oxime substituents including bastadin-3 (4), -4 (1), -9 (2), and -16 (3), hemibastadin-1 (6), aplysamine-2 (5), and psammaplin A (10) turned out to inhibit larval settling at 1 to 10 microM. Analogues of hemibastadin-1 (6) were synthesized and tested for structure activity studies. Debromohemibastadin-1 (8) inhibited settling of B. improvisus, albeit at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
89
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 50 publications
2
89
0
Order By: Relevance
“…In the latter study, found 2 exceptions to the general rule: the Red Sea sponge Axinella carteri and a Caribbean Stylissa species, both belonging to the family Axinellidae. These 2 species are known to contain bromopyrrole compounds including feeding-deterrent ones (Fedoreyev et al 1986, Assmann et al 2001b, Assmann & Köck 2002, Ortlepp et al 2007, and thus might rely on chemical anti-predator defense alone. Ferguson & Davis (2008) indicated the possibility that spicules of a size smaller than 100 µm deter the generalist sea urchin Centrostephanus rodgersii.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter study, found 2 exceptions to the general rule: the Red Sea sponge Axinella carteri and a Caribbean Stylissa species, both belonging to the family Axinellidae. These 2 species are known to contain bromopyrrole compounds including feeding-deterrent ones (Fedoreyev et al 1986, Assmann et al 2001b, Assmann & Köck 2002, Ortlepp et al 2007, and thus might rely on chemical anti-predator defense alone. Ferguson & Davis (2008) indicated the possibility that spicules of a size smaller than 100 µm deter the generalist sea urchin Centrostephanus rodgersii.…”
Section: Discussionmentioning
confidence: 99%
“…This finding implies that within a compound library, different mode of actions may be operating. 48 bastadin-9 (IC50 = 1.0 µM) 49 and synoxazolidinone C (IC50 = 2 µM). 29 The compounds also share similar structural features and antifouling activities with the natural antifouling phenyl ethers recently reported by Wang and co-workers.…”
mentioning
confidence: 99%
“…Bromotyrosine derivatives, polybrominated diphenyl ethers, subergorgic acid and so on were all isolated from sponges, which were promising sources of antifoulants. [33][34][35] Li et al [36] reported that 49 secondary metabolites, including diterpenoids, steroids and polyketides, were isolated from soft corals, gorgonians, brown algae and fungi. Twenty of the compounds were found to inhibit significantly the settlement of barnacle larvae at a concentration of 25 mg/L.…”
Section: Discussionmentioning
confidence: 99%